2022
DOI: 10.1073/pnas.2119381119
|View full text |Cite
|
Sign up to set email alerts
|

Cell size and polarization determine cytokinesis furrow ingression dynamics in mouse embryos

Abstract: Significance The final step of cell division, termed cytokinesis, comprises the constriction of a furrow that divides the cytoplasm to form two daughter cells. Although cytokinesis is well studied in traditional cell systems, how cytokinesis is regulated in complex multicellular settings and during cell-fate decisions is less well understood. Here, using live imaging and physical and molecular interventions, we find that the emergence of cell polarity during mouse embryo morphogenesis dramatically im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…However, the asymmetric ingression we observed in MDCK cells was more extreme compared to the other cell lines. A recent study showed that apical PAR proteins localize mutually exclusively to anillin in cells within developing mouse embryos suggesting they could compete for the same filamentous networks [ 49 ]. These proteins could be asymmetrically distributed prior to establishing full apicobasal polarity, which could cause anillin to be more broadly distributed along the asymmetrically ingressing cortex (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the asymmetric ingression we observed in MDCK cells was more extreme compared to the other cell lines. A recent study showed that apical PAR proteins localize mutually exclusively to anillin in cells within developing mouse embryos suggesting they could compete for the same filamentous networks [ 49 ]. These proteins could be asymmetrically distributed prior to establishing full apicobasal polarity, which could cause anillin to be more broadly distributed along the asymmetrically ingressing cortex (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although these cells establish apicobasal polarity in culture when grown to confluency [84], we imaged these cells at lower confluency, revealing that intrinsic mechanisms control ring ingression. Few studies have explored the mechanisms controlling the symmetry of ring closure, which is not well understood [44,49,[99][100][101]. The ring may close at least partially asymmetrically in many cell types, and the extent of asymmetry could reflect differences in cell size and fate in addition to adhesion to neighbouring cells [99].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokinesis is influenced by intrinsic and extrinsic factors that affect filament alignment for constriction and include polarity, cell–substrate adhesion and adherens junctions ( Higashi et al, 2016 ; Pinheiro et al, 2017 ; Dix et al, 2018 ; Chaigne et al, 2021 ; Gupta et al, 2021 ; Ozugergin et al, 2022 ; Paim and FitzHarris, 2022 ). Along with causing different rates of ingression, these factors can also cause ingression to be more asymmetric ( Figure 1C ).…”
Section: Differences In Cytokinesis Among Animal Cell Typesmentioning
confidence: 99%
“…However, in the vulval precursor cells, tissue geometry and adhesion play a stronger role ( Maddox et al, 2007 ; Bourdages et al, 2014 ). PARD6B is required for apicobasal polarity and asymmetric ingression in the early mouse embryo, and the localization of anillin and myosin is mutually exclusive with apically-enriched PARD6B ( Paim and FitzHarris, 2022 ). This mechanism differs from Drosophila epithelial cells where ingression is influenced by extrinsic forces transmitted through adhesion junctions ( Herszterg et al, 2014 ; Osswald and Morais-de-Sa, 2019 ; Buckley and St Johnston, 2022 ).…”
Section: Differences In Cytokinesis Among Animal Cell Typesmentioning
confidence: 99%